Unveiling entrepreneurial action: A meta-synthesis on effectuation and bricolage - Scazziota, V. V.; Andreassi, T.; Serra, F.; Esperança, J.; Guerrazzi, L. (2019 AOM Annual Meeting Proceedings, 2019)
Although bricolage and effectuation are the most cited theoretical approaches in the field of entrepreneurship, their research remain inconclusive with regard to their respective antecedents. In this study, we used meta-synthesis as a way to push the boundaries of both approaches and to reconcile the rich and fragmented evidence provided by case studies. This study extends the current theory by demonstrating which contextual antecedents and individual attributes were manifested in practice and explaining how they relate to actions of bricolage and effectuation, broadening our understanding of the issues of how and why they prevail, erstwhile called for in the literature.